Adaptive Fault Tolerant Control for Liquid Tank Process - Mehmet Arıcı; Tolgay Kara (International Journal of Applied Methods in Electronics and Computers, 2016)
Level control of liquids in coupled tanks is a basic requirement in many industrial processes. Liquid levels in tanks must be controlled accurately regardless of environmental circumstances. Minor faults in sensors, actuators or other system components that take place in processes where liquid level control is required can result in catastrophic consequences. In this case, a fault tolerant control system is needed. The controller must be either robust (passive) or in reconfigurable (active) type in order to compensate for the effect of actuator faults and maintain system reliability and performance. In this study, a water tank level control system and possible valve actuator faults are modelled. By designing different controllers and using modelled failures a simulation is constructed. To test the reconfigurable type controller performance against faults/failures, a model reference adaptive control system is implemented and compared with PI-controlled system.